Immune Sensing Mechanisms that Discriminate Self from Altered Self and Foreign Nucleic Acids - Bartok, Eva (Immunity, 2020)
All lifeforms have developed highly sophisticated systems equipped to detect altered self and non-self nucleic acids (NA). In vertebrates, NA-sensing receptors safeguard the integrity of the organism by detecting pathogens, dyshomeostasis and damage, and inducing appropriate responses to eliminate pathogens and reconstitute homeostasis. Effector mechanisms include i) immune signaling, ii) restriction of NA functions such as inhibition of mRNA translation, and iii) cell death pathways. An appropriate effector response is necessary for host defense, but dysregulated NA-sensing can lead to devastating autoimmune and autoinflammatory disease. Their inherent biochemical similarity renders the reliable distinction between self NA under homeostatic conditions and altered or exogenous NA particularly challenging. In this review, we provide an overview of recent progress in our understanding of the closely coordinated and regulated network of innate immune receptors, restriction factors, and nucleases to effectively respond to pathogens and maintain host integrity.